2020
DOI: 10.1021/acs.inorgchem.0c01835
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II) Phosphine/Mercapto Complexes: Their in Vitro Cytotoxicity Evaluation and Actions as Inhibitors of Topoisomerase and Proteasome Acting as Possible Triggers of Cell Death Induction

Abstract: In this paper, a series of new ruthenium complexes of the general formula [Ru(NS)(dpphpy)(dppb)]PF 6 (Ru1−Ru3), where dpphpy = diphenyl-2-pyridylphosphine, NS ligands = 2-thiazoline-2-thiol (tzdt, Ru1), 2-mercaptopyrimidine (pySm, Ru2), and 4,6diamino-2-mercaptopyrimidine (damp, Ru3), and dppb = 1,4-bis(diphenylphosphino)butane, were synthesized and characterized by elemental analysis, spectroscopic techniques (IR, UV/ visible, and 1D and 2D NMR), and X-ray diffraction. In the characterization, the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…Previous data on Ru naphthoquinone complexes incorporated with phosphorous-based ligands have shown excellent selectivity toward MDA-MB-231 cells as compared to MCF-10A cells . Selectivity toward MDA-MB-231 over MCF-10A cells was also seen by several reported Ru phosphine/mercapto complexes, though to a much lesser extent . However, studies on other Ru polypyridyl complexes with acac-based ferrocenyl β-diketonate ligands showed no selectivity toward cancerous HCT116 p53 +/+ cells over noncancerous ARPE-19 cells .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous data on Ru naphthoquinone complexes incorporated with phosphorous-based ligands have shown excellent selectivity toward MDA-MB-231 cells as compared to MCF-10A cells . Selectivity toward MDA-MB-231 over MCF-10A cells was also seen by several reported Ru phosphine/mercapto complexes, though to a much lesser extent . However, studies on other Ru polypyridyl complexes with acac-based ferrocenyl β-diketonate ligands showed no selectivity toward cancerous HCT116 p53 +/+ cells over noncancerous ARPE-19 cells .…”
Section: Discussionmentioning
confidence: 92%
“…81 Selectivity toward MDA-MB-231 over MCF-10A cells was also seen by several reported Ru phosphine/mercapto complexes, though to a much lesser extent. 82 However, studies on other Ru polypyridyl complexes with acac-based ferrocenyl β-diketonate ligands showed no selectivity toward cancerous HCT116 p53 +/+ cells over noncancerous ARPE-19 cells. 36 Similarly, other studies on bpy-based Ru complexes with similar acacbased ligands showed higher toxicity compared to our complexes when tested against cancerous cell lines like HL60, MIA PaCa-2, and DU-145 cells, but no studies regarding selectivity of these complexes toward cancerous vs non-cancerous cell lines have been mentioned by the authors.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Ruthenium(II) complexes designed in the present study were tested against several cancer cells, presenting important cytotoxic activity. Other recent studies have shown that complexes of ruthenium with different phosphine ligands can induce cytotoxic activity against cancer cell lines ( 54 56 ). Lapachol and its derivatives showed antiproliferative effects in different histological types of cells, including ovary, colon, lung, breast, leukemia, esophageal, cervical, melanoma, and prostate ( 7 , 57 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inevitable drug resistance is another limitation of the platinum drugs . Considering the disadvantages of platinum drugs, other metal-based anticancer compounds have been designed as alternatives to platinum drugs, especially ruthenium-based anticancer agents, which has shown great promising in cancer therapy due to their unique biological properties and low toxicity. …”
Section: Introductionmentioning
confidence: 99%